Results of a study on combustion of solids in an enclosed volume - T. P. Makarova; A. N. Baturo; Yu. N. Bezborodov (Омский научный вестник)
The paper presents the results of laboratory experiments to study the parameters of the gas environment during the combustion of wood, rubber and plastic under conditions that exclude oxygen access to the reaction area. A laboratory bench has been developed to create the conditions. Graphs of temperature changes and reduction of light transmission of combustion products accumulated in the upper part of the combustion chamber layer have been obtained. Changes of the controlled parameters are analysed and correlation dependences between them are obtained. The results obtained can be used as estimates for building prediction models of fire development in enclosed storage rooms, as well as for assessing the fire hazard of substances when burning in an enclosed volume.